Intangibles, Market Failure and Innovation Performance 2014
DOI: 10.1007/978-3-319-07533-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Intangible Assets and Investments at the Sector Level: Empirical Evidence for Germany

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Corrado et al (2014Corrado et al ( , 2017 takes the analysis to the industry level and investigates if and how intangibles affect sectoral growth. Empirical work using an expenditure-based approach to measurement has been mainly grounded in the theoretical framework set up by CHS (Crass et al, 2015;Crass & Peters, 2014;Marrano et al, 2009;Roth & Thum, 2013;Squicciarini & Le Mouel, 2012;van Ark et al, 2009).…”
Section: The Level Of Measuring Intangible Assetsmentioning
confidence: 99%
“…Corrado et al (2014Corrado et al ( , 2017 takes the analysis to the industry level and investigates if and how intangibles affect sectoral growth. Empirical work using an expenditure-based approach to measurement has been mainly grounded in the theoretical framework set up by CHS (Crass et al, 2015;Crass & Peters, 2014;Marrano et al, 2009;Roth & Thum, 2013;Squicciarini & Le Mouel, 2012;van Ark et al, 2009).…”
Section: The Level Of Measuring Intangible Assetsmentioning
confidence: 99%
“…Apart from measuring intangibles at the sectoral and total economy level, a number of firm-level surveys with special focus on intangibles were conducted (Awano et al, 2010a;Awano et al, 2010b;Perani and Guerrazzi, 2012;European Commission, 2014). Furthermore, there exists a number of studies analysing the impact of knowledge-based capital on firm performance based on pre-existing general firm surveys (Crass et al, 2014;Di Ubaldo and Siedschlag, 2020;Rammer et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the effect of IC investment is highly heterogeneous. At the sectoral level, IC investment largely concentrates in a few sectors (e.g., IT, finance and communication services) and therefore can boost these sectors to grow faster than others (Borgo et al, 2013; Corrado et al, 2014; Crass et al, 2015; Miyagawa & Hisa, 2013). At the firm level, it is found that firm‐specific characteristics such as size, age and human capital endowment are positively associated with the propensity and intensity of IC investment, which in turn contributes to the firm's productivity growth (Arrighetti et al, 2014; Chappell & Jaffe, 2018).…”
Section: Introductionmentioning
confidence: 99%